Impact of Covid-19 HRM Challenges on HRM Practices for Routing the Post Pandemic: A Study with Special Reference to Oil & Gas Companies in Oman - PORKODI, S; Al-Zawaidi, Azhaar Masoud; Al-Muharbi, Anood Mohammed; Al-Sarmi, Lamees Mohammed; Al-Shibli, Hafeedha Mohammed; Al-Rahbi, Wesal Nasser (Advances in Social Sciences Research Journal, 2021)
Human Resources Management is an important element to the success and progress of any organization, the uniqueness of HRM practices is considered as a possible competitive tool and the central value of the company. In this research, an attempt was made to study the impact of HRM challenges on post-COVID-19 HRM practices. The practices include health and safety, work schedule, cooperation communication, training, and recruitment and selection. The respondents of the study were different levels of managers working in oil and gas companies in Oman. An online questionnaire was used to collect data from 130 respondents. This research concludes that the level of HRM challenges has highly significant with the age group of the respondents. In addition, multiple linear regression was applied and the study revealed that three variables are highly significant with the post-COVID HRM practices. Those variables represent health issues in the Pandemic situation, difficulty in balancing between work and life, and difficulty in strategic focus during this pandemic. These variables underwent most of the post-COVID HRM practices in the Oil and gas companies in Oman.